Rush hours and urbanization - Tobias Seidel; Jan Wickerath (Center for Economic Studies and ifo Institute (CESifo), 2019)
We use a spatial general equilibrium model with potential commuting of workers between their place of work and their place of residence to analyze the effects of rush hours on the spatial allocation of employment and population, average labor productivity and the housing market. Abolishing traffic congestion during rush hours leads to a more urbanized economy as households move from the low-density countryside to the commuter belts of cities rather than from the city centers to the periphery. Employment, however, becomes more agglomerated in high-density large cities. This adjustment implies an increase of average labor productivity of 7.2 percent and higher inequality of housing costs.
Keywords: R12; R13; R41; 330; urbanization; commuting; traffic; congestion; spatial general equilibrium